The Relationship Between Peer Conformity and Bullying Behavior Among Students in A Public Senior High School in Jakarta - Santi Santi; Santa Maria Pangaribuan; Loritta Yemina; Lince Siringoringo (Nursing Current: Jurnal Keperawatan, 2025)
In Indonesia, approximately 25% of reported violence cases are related to the education sector, with 1,480 documented incidents of bullying in schools. Bullying behavior among adolescents may be influenced by peer conformity, in which individuals seek social acceptance by adapting to group norms and expectations. This study aimed to examine the relationship between peer conformity and bullying behavior among students. An analytical correlational design with a cross-sectional approach was employed, involving 139 respondents. Data was collected using two questionnaires: the Peer Conformity Questionnaire and the Bullying Behavior Questionnaire. The results indicated a significant association between peer conformity and bullying behavior (χ² = 29.165, p = 0.023). Based on these findings, it is recommended that teachers implement weekly student briefings, conduct monthly behavioral evaluations, provide positive reinforcement for students who demonstrate awareness and prevention of bullying, and apply disciplinary warnings for those involved in bullying. Moreover, anti-bullying education should be strengthened, and participation in extracurricular activities focused on bullying prevention should be encouraged, particularly for Grade X students.